The story of Coca-Cola - Bell, Lonnie (North Mankato, Minn. : Smart Apple Media, 2004)
Discusses the founding and development of Coca-Cola, which calls itself "the world's soft drink."
"A+."
Includes bibliographical references (p. 48) and index.
Horn Book, April 2004
6.1
5-8
Keywords: Coca-Cola Company -- History